Pemetaan Literatur Ilmiah Mengenai Internal Control over Financial Reporting (ICOFR): Pendekatan Bibliometrik Berbasis Database Scopus - Kamal Amarullah (CV. Ulil Albab Corp, 2025)
Internal Control over Financial Reporting (ICOFR) is an important element in ensuring the reliability of financial information. Although research on this topic has grown steadily since the introduction of the Sarbanes-Oxley Act (SOX), there is still a lack of systematic studies that map the intellectual structure and thematic development of ICOFR-related literature. This study aims to answer two main research questions: (1) what are the general characteristics, scientific contributions, and most influential documents in the literature on ICOFR; and (2) what are the key themes, the connections between topics, and the direction of conceptual development in ICOFR research based on co-occurrence network and thematic map analysis. A bibliometric method was applied to 272 publications collected from the Scopus database, and visual analysis was conducted using Bibliometrix in RStudio. The results show that most studies still focus on well-known topics such as material weakness, audit, and corporate governance, and that a small number of journals and authors dominate the field. However, there are signs of a shift toward more strategic and forward-looking topics. This study helps provide a clearer picture of the ICOFR research landscape and offers ideas for future interdisciplinary research opportunities.